When finances shake, do ethics break? The impact of financial instability on firm performance and CSR in Indonesian manufacturing - Choirul Istiyanto; Tastaftiyan Risfandy (Universitas Sebelas Maret, 2025)
This study examines the influence of corporate social responsibility on the company's financial performance during periods of financial instability. The sample of this study is manufacturing companies in the basic and chemical industries listed on the Indonesia Stock Exchange (IDX) for the 2014-2022 period. This study uses secondary data from the company's financial statements and annual reports. The test results show that during the period of financial instability, the relationship of corporate social responsibility to the company's financial performance weakens. This study proves that financial instability moderates the relationship between CSR and corporate financial performance. The results of this study show a linear and non-linear pattern in the relationship between CSR and financial performance during periods of financial instability. These findings emphasize the importance of managing CSR portfolios and prudence in resource allocation during periods of financial instability.